Playing the succession game to ensure family business continuity - Jorge, Sílvia (2021)
Family businesses are especially conflict-prone, since sibling rivalry and other emotional undercurrents sometimes cloud decision-making. One of the thorniest decisions is who will fill a founder’s shoes – especially if more than one family member wants the job. The costs of conflict can be high: consider the case of Reliance Industries, whose founder died without appointing a successor. His two sons fought so hard to succeed him that their mother had to split the company in two in order to save it. [...]